Community Based Tourism Analysis at Alamendah Tourism Village - Sarwani, Leanora Angelica Agatha; Hermawanti, Artin Ar.; Ramadhanty, Annisa; Furqan, Alhilal (E-Journal of Tourism, 2023)
Alamendah Tourism Village is an agronomic village, where most of the land is used for agricultural activities. Alamendah Tourism Village has begun to focus on developing product innovations and tour packages by utilizing the potential that exists in the village. The development of the Alamendah Tourism Village is inseparable from the active role of the local community. This paper aims to identify the steps in developing and maintaining CBT in Alamendah Tourism Village. This research uses a descriptive qualitative method. The data used in this study are primary and secondary. Primary data was used from interviews and field observations. While the secondary data used was obtained from e-books, scientific journals, news, and other documents. Based on the results of an analysis of the ten stages of community-built tourism both at the formation and development stages, most of the indicators contained in the ten stages have been fulfilled however there are still several indicators contained that have not been fulfilled in tourism activities organized by the community in Alamendah Tourism Village.